Sandstones of the Lower Cretaceous in Southern Peru - Yauli Cuadrado, Cynthia (2023)
The Lower Cretaceous in Peru had as its main characteristic intense sedimentation. This can be found in different country regions; one is Apurímac, where various geological formations are observed. This study aimed to review the mineral deposits and occurrences in the region of the Hualhuani formation with the influence of the Andahuaylas-Yauri Batholith. Describing the geological context, the presence of the Utupara, Antilla, Tumipampa, and Trapiche deposits, and the mineral occurrence of Pataypampa showed a mineralization with monzonite quartz stock within the Hualhuani formation; these sandstones are related to the presence of gold and copper deposits. Therefore, this area should be considered as an exploration guide for future mineral deposits. Likewise, a comparison is made with the Lo Prado and Veta Negra formations in Chile, where a similar geology is perceived, with which it is intended to support the subsequent exploration guides to the South of the country.